The Intention of Millennial Generation in Paying Zakat through Digital Payments - Muhamad Daniyal Al Athar; Mohammad Nur Rianto Al Arif (Faculty of Islamic Economics and Business of UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
The zakat management organization (OPZ) is currently making innovations following technological developments, making it easier to pay zakat through digital payments. One of the groups of people who use digital payments is the millennial generation. The millennial generation is also known as the generation that likes things that are easy and related to technology. This study aims to analyze how the millennial generation intends to pay for zakat through digital payments. The method used in this research is logistic regression. The results showed that the variable trust, perception variable, and convenience variable had a significant influence on the intention of the millennial generation to pay zakat through digital payments, while knowledge and motivation had an insignificant effect. This research result implies that OPZ must make a convenient application for the millennial generation in making zakat payments digitally.